The civil service career: its necessary observance for the regulation of collective bargaining of wages in the public sector in Peru - Luyo Rodríguez, María Eugenia (2020)
The issue of a regulation implementing the fundamental right of public servants to collective bargaining on wages still remains a pending challenge in our country. Taking this into consideration, and in order to propose solutions regarding the appropriate regulations on this matter, this article seeks to raise awareness on the public administration career as a constitutionally right, wich content deserves special attention and observance for the purpose of regulating collective bargaining on remuneration in the public sector, after noting the negative and positive impacts on the structure of the Public Administration resulting from the compliance and non-compliance with the foregoing.